Humanitarian intervention and the responsibility to protect who should intervene? - Pattison, James, 1980- (Oxford : Oxford University Press, 2010)
This text considers who should undertake humanitarian intervention in response to an ongoing or impending humanitarian crisis. It develops a normative account of legitimacy to assess not only current interveners, but also the desirability of potential reforms to the mechanisms and agents of humanitarian intervention.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Humanitarian intervention; Conflict management; Security, International